An investigation on parallel and cluster computing with .net framework - Che Yung Xuen (2023)
This thesis reports the investigation on how implement parallel computing environment in Microsoft Windows environment. The project scope covers the tools collection, software implementation procedure design and building of a computer cluster by using Windows HPC Server 2008.